An optimized numerical tornado simulator and its application to transient wind-induced response of a long-span bridge. Issue 227 (August 2022) - Feng, Yu; Hao, Jianming; Han, Wanshui; Su, Quanke; Wu, Teng
Abstract: The long-span bridges in the tornado-prone area would be potentially struck by extreme transient winds. In this study, the tornado-like wind field is simulated by the numerical Ward-type tornado simulator based on computational fluid dynamics (CFD) techniques. To minimize the discrepancy between the simulated and field-measured tornado winds, the optimization strategy is developed to achieve optimal parameters of the numerical Ward-type tornado simulator, namely the inflow angle ( θ ) and translation speed ( V T ). To facilitate the optimization process, a multi-fidelity surrogate model is utilized to effectively integrate both low-fidelity and high-fidelity data for accurate and efficient simulations. Specifically, the cokriging model is constructed by the CFD data associated with both low-cost Reynolds-averaged Navier-Stokes (RANS) equations and high-cost large-eddy simulation (LES) techniques. The "best" parameters (i.e., θ and V T ) based on the multi-fidelity surrogate model are input to the numerical Ward-type tornado simulator (using LES technique), and the obtained wind field matches excellently with the field measurements. Finally, the transient wind field generated using the validated numerical Ward-type tornado simulator is employed as the dynamic inputs to the finite element (FE) model of a long-span bridge, and the results highlight the important contribution of the transient bridge aerodynamics. Highlights: A optimization method to achieve optimal parameters of the numerical Ward-type tornado simulator is proposed. Multi-fidelity surrogate model to integrate both low-fidelity and high-fidelity data of tornado-like wind is implemented. The aerostatic and aeroelastic analysis of a long-span bridge subjected to the tornadic wind field are studied.